Burnout Syndrome in Primary Health Care professionals during the COVID-19 pandemic (Acta Scientiarum. Health Sciences, 2023)
Workers in Primary Health Care (PHC) play a key role in coping with COVID-19, which required personal and work-flow changes, causing physical and emotional overload and stress, which could lead to Burnout Syndrome (BS). The objective of this study was to check the prevalence of BS in health professionals working in PHC in the municipality of Curitibanos, state of Santa Catarina, Brazil. The research was carried out between November 2020 and May 2021, a sociodemographic questionnaire, and the Brazilian version of the Maslach Burnout Inventory - Human Services Survey (MBI-HSS), which contains 22 questions and three dimensions - Emotional Exhaustion (EE), Depersonalization (DP) and Personal Fulfillment (PF), were applied. Data were collected and analyzed descriptively with subsequent statistical comparison. Participants were50 volunteers aged 40.1 ± 9.5 years, time in the profession of 10.8 ± 7.9 years. Results of the MBI-HSS showed the prevalence of risk was moderate for EE and high for DP and PF. However, no significant difference was detected between the MBI-HSS dimensions and sociodemographic variables. In conclusion, the prevalence of risk was 17.6+11.4 points in EE (moderate); 6.6+5.0 points in DP (moderate) and 36.8+6.6 points in RP (high), indicating that the evaluated population already demands some need for contingency or preventive care because it has a clear predisposition to BS. However, there was no statistical association with sociodemographic variables.